Achievements in the Study of Marine Low‐Molecular Weight Biologically Active Metabolites from the Vietnamese Territorial Waters as a Result of Expeditions aboard the Research Vessel 'Akademik Oparin' (2004–2017). Issue 7 (13th June 2019) - Yurchenko, Ekaterina A.; Yurchenko, Anton N.; Van Minh, Chau; Aminin, Dmitry L.
Abstract: Until 2004, the secondary metabolites of marine organisms of the Vietnamese territorial waters had been studied very poorly. Only four new compounds were isolated from 1977 to 2003. Joint Russian‐Vietnamese expeditions aboard the research vessel 'Akademik Oparin' made it possible to study in detail the chemical diversity of marine micro‐ and macroorganisms. As a result of five expeditions, more than 250 low‐molecular weight natural compounds, including 117 new metabolites, were isolated from marine invertebrates and microfilamentous fungi. Their biological activities, such as cytotoxic, cytoprotective, and antioxidant activities, were investigated. Information about the structure and biological activity of the compounds, the source for their isolation and the geographical location of the objects is summarized in this review. Abstract :